Multidisciplinary Optimization for Active Aero-elastic Morphing Wings - Zhang, Hao; Sun, Ruisheng; Zhao, Ri (Chinese Control Conference, 2018)
This paper presents a multidisciplinary optimization design for aero-elastic morphing regional jet wings in an integrated design system. In terms of aircrafts' design requirements, we provide an optimization scheme including airfoil, structure parameter and pre-deformation shape (jig shape). The ideal wing shape is optimized to reach minimum lift-induced drag and minimum wing weight through aerodynamic, structural and aero-elastic subsystems. The aerodynamic subsystem, based on an inverse vertex lattice method, is utilized to find the optimal mean camber as well as wing twist subject to both aerodynamic performance and minimum lift-induced drag. The structural subsystem takes Lagrange method to optimize morphing wing structure for minimum wingbox weight in the condition of deformation constraints. Aerodynamic force is loaded to the current wing structure in the aero-elastic subsystem, which optimizes current shape to jig shape. The analysis results of the application case illustrate that the desired active aero-elastic morphing wing scheme is successfully achieved through the proposed multidisciplinary optimization design.